THE ROLE OF PHYSICAL THERAPY IN THE RECOVERY OF THE PATIENT WITH DOWN SYNDROME - Ștefan Crețu; Florian Benedek (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
In this scientific article we want to highlight the importance of Kinetotherapy in Down Syndrome. In order to be able to work with people with Down Syndrome, first of all it is necessary that we understand these people. It is not an easy job and it requires a lot time for these people to learn or improve certain motric skills. An example is that for a person with Down Syndrome a simple action such as "buttoning clothes" can take months and even several years. Our role as Kinetotherapists is to be able to help these people live as much as possible close to normal.